Framework of Six Sigma implementation analysis on SMEs in Malaysia for information technology services, products and processes - Wong, Whee Yen (2015)
For the past two decades, the majority of Malaysia’s IT companies have been widely adopting a Quality Assurance (QA) approach as a basis for self-improvement and internal-assessment in IT project management. Quality Control (QC) is a comprehensive top-down observation approach used to fulfill requirements for quality outputs which focuses on the aspect of process outputs evaluation. However in the Malaysian context, QC and combination of QA and QC as a means of quality improvement approaches have not received significant attention. This research study aims to explore the possibility of integrating QC and QA+QC approaches through Six Sigma quality management standard to provide tangible and measureable business results by continuous process improvement to boost customer satisfactions.